Edukasi Ibu Hamil dan Ibu Post Partum tentang Bahaya Depresi Post Partum di Puskesmas Kassi-Kassi - Firawati Firawati; Hasnaeni Hasnaeni; Jamila Kasim (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
The postpartum period is a recovery period, postpartum care is needed so that mothers can make psychological adaptations in the postpartum period, Postpartum depression is depression that occurs in women after giving birth, which occurs within a period of 4 (four) weeks, several months or even several years if not treated, the purpose of this community service is to provide education to pregnant women and postpartum mothers regarding the prevention of the dangers of postpartum depression, this activity is to increase mothers' understanding of the dangers of postpartum depression. This community service activity was attended by pregnant women and postpartum mothers at the Kassi-Kassi Health Center which was attended by 18 people. This activity method was carried out twice by providing a pre-test, lecture and continued post-test by filling out a questionnaire. In the evaluation, interviews were conducted with pregnant women and postpartum mothers to determine the dangers of postpartum depression. The results achieved in community service activities at the Kassi-Kassi Health Center were that postpartum mothers gained knowledge about the dangers of postpartum depression and there was an increase in knowledge about the dangers of postpartum depression. The pre-test results were 58.82%, there was an increase in the post-test which showed post-test knowledge of 82.35%. The conclusion is that education for pregnant and post-partum mothers can prevent post-partum depression.